ქართული ტერმინოლოგიური მუშაობის ასპექტები - საღინაძე/ Saginadze, რუსუდან/ Rusudan (ივანე ჯავახიშვილის სახელობის თბილისის სახელმწიფო უნივერსიტეტის გამომცემლობა, 2022)
In the conditions of modern globalization, when new fields are created or introduced to the country, the mechanism of selection and establishment of terms has not yet been fully developed. Therefore, in many cases, the borrowing of terms relevant to this or that field reveals a spontaneous character. At the same time, a large amount of technical literature is translated, and new terms appear, including those that are calqued or transferred directly, without translation. The old term frequently continues to exist along with the new one. The object of our research is one of the main problems in modern Georgian technical terminology – the standardization and normalization of the variants of borrowed terms. This is not a new phenomenon. Specialists point to this problem even today: "Terminological diversity is the main difficulty, due to which the "growth of the language" is hindered" (Karosanidze 2020). The article briefly discusses the role of previous terminologists in the formation and development of Georgian technical terminology; According to the dictionary material and the data available in various publications, several groups of borrowed technical parallel terms are separated and analyzed: Old and new terms: carbonic acid (nakhshirzhangi) || carbon monoxide (nakhshirbadis monoxidi) (CO); carbonic acid (nakhshiror-zhangi) || carbon dioxide (nakhshirbadis dioxidi) (CO2)... Foreign and Georgian terms: intoxication (intoxicatia) || poisoning (motsamvla); toxic (toxikuri) || toxic (toxiuri) || poisonous (momtsamlavi) || poisonous (momwamvleli); intoxicated (intoxirebuli) || poisoned (motsamluli); Lead glaze (tqviis glazuri) || Lead glazing (tqviis mochi-kureba)... Calqued terms: Refrigerant (matsivaragenti) (Russ. Хладагент); refrigerant agent (samatsivro agenti) (Russ. холодильный агент) („Technical Terminology“ 1982)... There are also variants of Georgian (Georgianized) terms determined by various factors: a) Phonetically determined: to spray (sheskhureba) || to spray (sheshskhureba) – to spray („sheskhureba“) is correct (Saghinadze 2006)... b) Semantically determined (formed with different affixes): energy efficiency (energoefekturoba) || Energy efficiency (energoefektianoba) – both are considered to be correct by specialists in the field D. Chomakhidze, K. Tskhakaya (Chomakhidze, Tskhakaya 2015)... This article concludes that analyzing more extensive material representing variants of borrowed technical terms allows us to identify standard issues and, more generally, to plan the ways of solving certain problems.
Aspects of Georgian Terminological Work
Keywords: ტერმინოლოგია; ნორმატიული; ტექნიკური; ლექსიკონი; სინონიმია ტერმინოლოგიაში; Terminology; Normativ; Technical Dictionary; Synonimy in Terminology